2014
DOI: 10.1016/j.ijheatmasstransfer.2013.09.020
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigation of heat transfer enhancement in a pipe partially filled with a porous material under local thermal non-equilibrium condition

Abstract: 11This paper examines numerically the heat transfer enhancement in a pipe 12 partially filled with a porous medium under Local Thermal Non-Equilibrium 13(LTNE) condition. The flow inside the porous material is modelled using the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
64
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 131 publications
(67 citation statements)
references
References 33 publications
3
64
0
Order By: Relevance
“…(3b) and (3c) are equivalent to model A of Yang and Vafai [31], which has been also used in the investigations of partially filled channels [16,29]. It is emphasised here that previous works [14][15][16] have demonstrated that the choice of porous-fluid boundary condition has significant effects upon the thermal behaviour of the system. In order to make analytical progress with the energy equations (2a) and (2b), their left hand sides should be evaluated.…”
Section: Governing Equationsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3b) and (3c) are equivalent to model A of Yang and Vafai [31], which has been also used in the investigations of partially filled channels [16,29]. It is emphasised here that previous works [14][15][16] have demonstrated that the choice of porous-fluid boundary condition has significant effects upon the thermal behaviour of the system. In order to make analytical progress with the energy equations (2a) and (2b), their left hand sides should be evaluated.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The latter, however, is regarded as local thermal non-equilibrium (LTNE), or two-energy equation model [11,12]. Although LTE model [11] has been used extensively in heat transfer analyses [11], LTNE model is receiving an increasing attention from the research community [13][14][15][16]. This stems from the fact that in the emerging fields such as MEMS and biotechnology as well as some classical areas, such as chemical and nuclear engineering, the accuracy of the analysis is of primary importance [12,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate work Yang and Vafai [34] analysed the validity of local thermal equilibrium in a partially filled channel with constant heat flux walls and under five different interface models. Mahmoudi and Karimi [35] considered a partially filled pipe under constant wall temperature boundary condition. They numerically solved the Darcy-Brinkman-Forshheimer model of fluid flow along with the two-equation energy transport and interface models of A and B [35].…”
mentioning
confidence: 99%
“…Alkam et al researched the heat transfer in parallel plates with porous inserts and the effects of thermal conduction ratio, Darcy number, and microscopic inertial coefficient were presented [24]. A local thermal non-equilibrium model is another research interest [25][26][27]. Besides, there is experimental research about heat transfer of air or water in ducts or channels with porous inserts or ribs [28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%